2020
DOI: 10.4049/immunohorizons.2000044
|View full text |Cite
|
Sign up to set email alerts
|

Adenomatous Polyposis Coli Modulates Actin and Microtubule Cytoskeleton at the Immunological Synapse to Tune CTL Functions

Abstract: Adenomatous polyposis coli (Apc) is a cell polarity regulator and a tumor suppressor associated with familial adenomatous polyposis and colorectal cancer. Apc involvement in T lymphocyte functions and antitumor immunity remains poorly understood. Investigating Apc-depleted human CD8 T cells and CD8 T cells from Apc Min/+ mutant mice, we found that Apc regulates actin and microtubule cytoskeleton remodeling at the immunological synapse, controlling synapse morphology and stability and lytic granule dynamics, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 58 publications
4
39
0
Order By: Relevance
“…Hence, these data suggest that the association of NFAT with the microtubule network could facilitate concentration of this transcription factor around the nucleus and/or its interaction with nuclear pores. In agreement with a functional link between NFAT and the microtubules, we have also observed that knockdown of several proteins that control the appropriate organization of the microtubule network, such as the polarity regulators Apc and Dlg1 and the actincytoskeleton linker ezrin, impairs NFAT nuclear translocation and transcriptional activity Aguera-Gonzalez et al, 2017;Juzans et al, 2020). Altogether, these data underscore the involvement of microtubules in driving NFAT nuclear localization.…”
Section: Role Of the Cytoskeleton In Signaling To The Nucleussupporting
confidence: 85%
See 4 more Smart Citations
“…Hence, these data suggest that the association of NFAT with the microtubule network could facilitate concentration of this transcription factor around the nucleus and/or its interaction with nuclear pores. In agreement with a functional link between NFAT and the microtubules, we have also observed that knockdown of several proteins that control the appropriate organization of the microtubule network, such as the polarity regulators Apc and Dlg1 and the actincytoskeleton linker ezrin, impairs NFAT nuclear translocation and transcriptional activity Aguera-Gonzalez et al, 2017;Juzans et al, 2020). Altogether, these data underscore the involvement of microtubules in driving NFAT nuclear localization.…”
Section: Role Of the Cytoskeleton In Signaling To The Nucleussupporting
confidence: 85%
“…For instance, silencing of Dlg1 or Apc results in impaired F-actin remodeling, microtubule disorganization, and impaired centrosome and CD3 polarization at the synapse (Round et al, 2005;Humphries et al, 2012;Aguera-Gonzalez et al, 2017;Juzans et al, 2020). Therefore, Dlg1 and Apc modulate CTL immunological synapse formation and function, consequentially influencing both the lytic granule delivery to the synapse and the ability to kill target cells (Silva et al, 2015;Juzans et al, 2020). In addition, the impairment of actin regulators, such as WASP or the Arp2/3 complex, results in altered target cell elimination (De Meester et al, 2010;Randzavola et al, 2019).…”
Section: Lytic Granule Releasementioning
confidence: 99%
See 3 more Smart Citations